Metal oxide-coated three-dimensional graphene prepared by the use of metal-organic frameworks as precursors - Cao, Xiehong (2014)
A simple method for the preparation of metal-oxide-coated three-dimensional (3D) graphene composites was developed. The metal–organic frameworks (MOFs) that served as the precursors of the metal oxides were first synthesized on the 3D graphene networks (3DGNs). The desired metal oxide/3DGN composites were then obtained by a two-step annealing process. As a proof-of-concept application, the obtained ZnO/3DGN and Fe2O3/3DGN materials were used in a photocatalytic reaction and a lithium-ion battery, respectively. We believe this method could be extended to the synthesis of other metal oxide/3DGN composites with 3D structures simply through the appropriate choice of specific MOFs as precursors.